The effect of intermittent fasting on the clinical and hematological parameters of patients with sickle cell disease: A preliminary study - Ahmed, Khalid; Abdu, Yasamin; Khasawneh, Sief; Shukri, Ahmed; Adam, Ehab; Mustafa, Salma; Affas, Mohammad; Mohamed Ibrahim, Mohamed Izham; Al Zayed, Abdullah; Yassin, Mohamed A. (Frontiers in Medicine, 2023)
Sickle cell disease is a genetic disorder that frequently presents with vaso-occlusive crisis (VOC). Most patients with sickle cell disease in Qatar are Muslims; hence, they practice intermittent fasting during the holy month of Ramadan. However, there is a paucity of literature describing the effect of intermittent fasting on the occurrence of severe VOC. As a result, there is a lack of guidelines or standardized protocols that can help physicians advise patients with sickle cell disease who wish to practice intermittent fasting. Therefore, this study’s aim was to investigate the effect of intermittent fasting on the clinical and hematological parameters of individuals with sickle cell disease. We conducted a retrospective study for 52 Muslim patients with sickle cell disease in Qatar aged ≥18 years who were confirmed to be fasting during the holy month of Ramadan during any of the years 2019-2021. The difference in the occurrence of severe VOC, hemolytic crisis, and other clinical, hematological, and metabolic parameters were studied one month before, during, and one month after the intermittent fasting of Ramadan using the patient's medical records. Mean (sd), median (IQR), and frequency (%) described the data. One-way with repeated measures ANOVA with a Greenhouse-Geisser correction and Friedman tests (*) were used at alpha level 0.05. The study participants' mean (sd) age was 31.1(9.2) years, 51.9% were males, and 48.1% were females. Roughly seventy percent of the participants were of Arab ethnicity, while the rest were either African or Asian. Most of the patients were homozygotes (SS) (90.4%). The median number of severe VOC (P=0.7) and hemolytic crisis (P=0.5) was not found to be significantly different before, during, or after Ramadan. Significant differences, however, were found in platelet count (P=0.003), reticulocyte count (P<0.001), and creatinine level (P=0.038) with intermittent fasting. In this preliminary study, intermittent fasting does not seem to influence the rate of occurrence of severe vaso-occlusive crisis or hemolytic crisis in patients with sickle cell disease; however, it can be associated with differences in platelet count, reticulocytes count, and creatinine level.